A New Video Summarization Approach Using Object Density Based Image Similarity for Smart City Applications - Altundogan, Turan Goktug; Karakose, Mehmet; Mert, Fatih (Institute of Electrical and Electronics Engineers Inc., 2025)
Summarization approaches are currently proposed solutions that focus on meaningfully reducing different types of data such as text, audio, and video. Many techniques such as machine learning, signal processing, image processing, computer vision, and deep learning can be used to develop summarization approaches. In this study, we performed object detection on videos that can be used in smart city applications using a pretrained YOLOv8 model. As a result of the object detection, we created a feature vector for each image frame by using the location information covered by the classes used in the object detection process. Then, we used several different approaches to determine the reference feature vector for the video. Finally, we calculated the cosine similarities of the feature vector for each frame to this reference feature vector using different methods. With the method we developed, we presented a similarity-focused summary created by selecting the video frames expressed with maximum similarity. We also developed an evaluation approach to evaluate the summaries we presented, comparing the overall heat maps of the video with the heat maps of the summary videos. Experimental results demonstrate the efficiency of our summarization approaches. © 2025 IEEE.
29th International Conference on Information Technology, IT 2025 -- 19 February 2025 through 22 February 2025 -- Zabljak -- 207747
Keywords: Image Similarity; Object Detection; Smart City; Video Summarization